Collaborative Learning Activities For Form One Science A Guide For Teachers (Based On The KSSM Curriculum) - Venosha Ravana; Sarala Thulasi Palpanadan (Penerbit UTHM, 2023)
This book acts as an instructional support mainly for science subject teachers who are looking to implement collaborative learning for their students. The content of the book has been designed to help teachers in every aspect of collaborative learning with various descriptions, sample activities, ready-to-use materials such as two types of feedback forms, a template for a self-reflective journal entry and also a checklist for a collaborative learning lesson. The writers hope that teachers will be able to practise the collaborative learning approach more profoundly in Malaysian secondary schools with, the help of this book.